2003
DOI: 10.1093/pcp/pcg157
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of an Ozone-Sensitive and Jasmonate-Semi-Insensitive Arabidopsis Mutant (oji1)

Abstract: A novel ozone-sensitive mutant was isolated from Arabidopsis T-DNA tagging lines. This mutant revealed severe foliar injury and higher ethylene emission than the wild type under ozone exposure. The ozone-induced injury and ethylene emission were suppressed by pretreatment with aminoethoxyvinyl glycine, an inhibitor of ethylene biosynthesis, both in this mutant and wild-type plants. Pretreatment with methyl-jasmonate (MeJA) at 10 micro M, however, suppressed the ozone-induced ethylene emission and foliar injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 44 publications
1
54
0
2
Order By: Relevance
“…Interestingly, JA signaling is also linked to ROS. For example, JA induces the accumulation of antioxidant pathways, and in a JA-deficient Arabidopsis mutant (opr3) the induction of these pathways upon ozone exposure is abolished (Sasaki-Sekimoto et al, 2005), and oji1, a JA-insensitive mutant, is hypersensitive to O 3 treatments (Kanna et al, 2003). On the other hand, JA generates H 2 O 2 , an agent we found to activate MPK7, as a secondary signal for the activation of defense genes (Orozco-Cardenas and Ryan, 1999;Orozco-Cardenas et al, 2001).…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly, JA signaling is also linked to ROS. For example, JA induces the accumulation of antioxidant pathways, and in a JA-deficient Arabidopsis mutant (opr3) the induction of these pathways upon ozone exposure is abolished (Sasaki-Sekimoto et al, 2005), and oji1, a JA-insensitive mutant, is hypersensitive to O 3 treatments (Kanna et al, 2003). On the other hand, JA generates H 2 O 2 , an agent we found to activate MPK7, as a secondary signal for the activation of defense genes (Orozco-Cardenas and Ryan, 1999;Orozco-Cardenas et al, 2001).…”
Section: Discussionmentioning
confidence: 77%
“…It has been shown that the lesion propagation in O 3 damage is under hormonal control (Overmyer et al, 2000;Rao et al, 2000Rao et al, , 2002Moeder et al, 2002;Kanna et al, 2003). Both jasmonateinsensitive (jar1 and coi1) and ET-overproducing mutants (eto1 and eto2) are O 3 sensitive as a result of lesion propagation, whereas the ET-or SA-insensitive mutants (etr1, ein2, npr1, and NahG) are O 3 tolerant.…”
Section: Is Rcd1 An Ozone Sensitive or Hormone Mutant?mentioning
confidence: 99%
“…Both jasmonateinsensitive (jar1 and coi1) and ET-overproducing mutants (eto1 and eto2) are O 3 sensitive as a result of lesion propagation, whereas the ET-or SA-insensitive mutants (etr1, ein2, npr1, and NahG) are O 3 tolerant. Furthermore, the mutants and accessions that have first been described as O 3 sensitive have also turned out to be partially JA insensitive (oji1, rcd1, and Cvi-0) or ET overproducers (rcd1) (Overmyer et al, 2000;Rao et al, 2000;Kanna et al, 2003). Moreover, the endogenous ROS production triggered by O 3 is ET dependent (Overmyer et al, 2000;Moeder et al, 2002;Wohlgemuth et al, 2002;Kanna et al, 2003).…”
Section: Is Rcd1 An Ozone Sensitive or Hormone Mutant?mentioning
confidence: 99%
See 1 more Smart Citation
“…Jasmonate (JA) has been implicated in signaling in response to both biotic and abiotic stresses (Balbi and Devoto, 2008;Wasternack, 2006;2007). Wounding and pathogen infection, or exposure to ozone, cause endogenous JA accumulation (Howe, 2004;Kanna et al, 2003;Rao et al, 2000;Vijayan, et al, 1998;Wasternack, 2006). Heat stress also induces the JA signal transduction pathway (Clarke et al, 2009).…”
Section: Introductionmentioning
confidence: 99%